Development of smart phone-enabled platform for virtual presence - Xin, Wen Qian (2017)
This paper introduces the design and process of the Final Year Project. A smart phone- enabled platform to view, explore and share virtual experiences using Virtual Reality technology. Additionally, it also supports pc platform. The aim of this project is to develop this platform to support upcoming Photonics Singapore Conference. This paper also discusses various technology, methodology and framework used in building this system.